Partnerships and Opportunities for a New Green Forest Economy in Lao PDR : Sustaining Forest Landscapes and Livelihoods - World Bank; International Finance Corporation (World Bank, Washington, DC, 2019)
Lao People's Democratic Republic (Lao PDR) has a comparative advantage in natural capital, which has fueled economic growth averaging around 8 percent per annum since 2000. The natural resource endowment comprises half of the country's wealth. Although forest cover declined 3.6 percent between 2005 and 2015, Lao PDR still has among the highest forest cover percentage of countries in the region, and the value of timber and non-timber forest products is 10,740 US Dollars per capita. Inefficiencies, including overuse, under-budgeting, and unsustainable and unscientific management, have led to a reduction in forest cover, natural wealth, and public revenues. Lao PDR's recent policy reforms, institution-building and community engagement aim to build a new foundation to sustain the Lao forest estate and the people and sectors that depend on it, including for tourism, agriculture, energy, water, fisheries, and wood products. Lao PDR's ambitious forest sector reforms aim to achieve financially and environmentally sustainable, resilient, and inclusive economic growth, especially through credible private sector investors. This reform agenda accompanies the Government of Lao PDR's (GoL) plan to expand forest cover to 70 percent from the current 58 percent, which will help to reduce poverty, create green jobs and livelihoods, support local industry and expand participatory sustainable forest management (SFM) and forest restoration, as well as to meet Lao PDR's Nationally Determined Contribution (NDC) to climate action. Auspiciously, credible private sector commercial plantation investors are also starting to scale up investment in the country.